Membangun Kesadaran Digital: Edukasi Hoaks dan Disinformasi dengan Pendekatan Teknologi bagi Siswa SMKN 2 Jombang - Mu minin, Mu minin; Maisaroh, Siti (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The rapid development of digital technology has significantly impacted the pattern of information dissemination, including among students. At SMKN 2 Jombang, the low level of digital literacy among students makes them vulnerable to hoaxes and disinformation circulating on social media. A lack of understanding of information verification and the absence of formal education on identifying hoaxes are key challenges in fostering digital awareness. To address this issue, the program